Short chain fatty acids and monocarboxylate transporters in irritable bowel syndrome - Ernst Fredericks,; Reza Theunissen,; Saartjie Roux, (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Gut microbiota ferments indigestible food that rests in the colon to produce short-chain fatty acids (SCFAs) acetate, propionate, and butyrate. Colonic SCFA stimulate the synthesis of serotonin which is central in irritable bowel syndrome (IBS) pathophysiology. Reduced SCFA have been linked to specific IBS symptoms like colonic hyperalgesia and hypersensitivity. SCFA enter the colonocyte mainly via 2 energy-dependent monocarboxylate transporters, MCT1 (SLC16A1) and SMCT1 (SLC5A8). We investigated specific gut microbiota, SCFA concentrations, and monocarboxylate transporter mRNA expression in patients with IBS. Material and Methods: A total of 30 IBS patients—15 constipation-predominant (C-IBS) and 15 diarrhoea-predominant (D-IBS)—and 15 healthy controls were recruited. Bacteroidetes and Bifidobacterium species were analyzed using quantitative polymerase chain reaction (qPCR) on stool samples. SCFA concentrations were determined by gas chromatography/mass spectroscopy of stool samples. Monocarboxylate transporter mRNA was quantified by qPCR on colon biopsy specimens. Results: Bacteroides was significantly increased in the D-IBS group compared with the C-IBS group and healthy controls. Bifidobacterium was significantly reduced in both IBS groups. SCFA ratios were altered in both IBS groups with a reduction of all 3 measured SCFA in C-IBS and acetic acid in D-IBS. MCT1 and SMCT1 were significantly reduced in C-IBS and D-IBS. Conclusion: In agreement with findings of previous studies, the microbiota assessed were significantly altered inferring dysbiosis in IBS. SCFA and their ratios were significantly altered in both IBS groups. SCFA transporters, MCT1 and SMCT1 were significantly reduced in both IBS groups, suggesting reduced colonocyte SCFA transfer. SCFA availability and transfer into the colonocytes may be important in IBS pathogenesis and should be prospectively studied. Cite this article as: Fredericks E, Theunissen R, Roux S. Short chain fatty acids and monocarboxylate transporters in irritable bowel syndrome. Turk J Gastroenterol 2020; 31(12): 840-7.